If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (3x + 2) = 26 Reorder the terms: X + (2 + 3x) = 26 Remove parenthesis around (2 + 3x) X + 2 + 3x = 26 Reorder the terms: 2 + X + 3x = 26 Solving 2 + X + 3x = 26 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + X + -2 + 3x = 26 + -2 Reorder the terms: 2 + -2 + X + 3x = 26 + -2 Combine like terms: 2 + -2 = 0 0 + X + 3x = 26 + -2 X + 3x = 26 + -2 Combine like terms: 26 + -2 = 24 X + 3x = 24 Add '-3x' to each side of the equation. X + 3x + -3x = 24 + -3x Combine like terms: 3x + -3x = 0 X + 0 = 24 + -3x X = 24 + -3x Simplifying X = 24 + -3x
| Y=1/2x-8 | | x-(1+x)+2x=-x+1 | | -11.1=8.1+v/6 | | 375=900-300p | | 2-sec^2(X)=2tan^2(X) | | T/8=13 | | 4x-6*-2=15 | | W^2-6w-66=0 | | 2log(x-1)=5log(y+2) | | (4*5)/5+4=c | | logx+3logy=0 | | 5*4/5+4 | | (10n+10)-10=10 | | 3*-4-6/x=12 | | X^4+4.33X^3-10.34X^2-54.35X-51.67=0 | | 10n+10-10=10 | | 4s-3t=Ifors | | -2x+3x=-15 | | w(3w+2)-2(w^2-8)=w(w+5)-6w+7 | | H+3/4=78 | | 3x^2+x=-11x | | 6/x=3/5 | | 5+2*x=2*x+5 | | 5+2*x=5+(2x) | | T+5=23 | | 8d+b/2b+2d | | 5+2*x=(5-2)x | | 2p^2+2=6p | | 2x+0,1-4*(1-4x)=8x-4,4 | | 14x+47=23 | | (4x+1)(3x-6)=0 | | 5+2*x=7x |